Analisis Sita Jaminan (Conservatoir Beslag) terhadap Tanah dan Bangunan yang Diagunkan untuk Meminjam Kredit Usaha pada PT. BPR Sumber Pangasean (Bank BSP), Tbk. Kantor Cabang Bandar Jaya (Studi Perkara Nomor: 15/Pdt.g.s/2020/PN Gns) - Angga Dwi Saputra (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
One example of the implementation of confiscation of collateral (conservatoir beslag) is the confiscation of collateral (conservatoir beslag) of land and buildings that are used as collateral to borrow business loans from PT. BPR Sumber Pangasean (Bank BSP) Tbk. The Bandar Jaya Branch Office based on Number: 15/Pdt.GS/2020/PN Gns stated that it accepted and granted the Plaintiff's claim entirely stating that by law the defendant's actions were a breach of contract to the Plaintiff. The problem of this research is how to implement the confiscation of collateral (conservatoir beslag) on land and buildings that are pledged to borrow business loans at PT. BPR Sumber Pangasean (Bank BSP), Tbk. Bandar Jaya Branch Office based on Decision Number: 15/Pdt.GS/2020/PN Gns? and What are the legal consequences of confiscation of collateral (conservatoir beslag) on land and buildings that are used as collateral to borrow business loans from PT. BPR Sumber Pangasean (Bank BSP), Tbk. Bandar Jaya Branch Office based on Decision Number: 15/Pdt.GS/2020/PN Gns?. The research method uses a normative and empirical juridical approach. The types of data used are secondary data and primary data. Collecting data through library research (library research) and field research (field research). The data analysis used is juridical qualitative. The results of the study show that the execution of the security confiscation (conseervatoir beslag) on land and house buildings on it which has become the object of mortgage rights based on Decision Number: 15/Pdt.GS/2020/PN Gns cannot be carried out. Based on the principle of confiscation, it is prohibited to confiscate goods that have been pledged or pledged as collateral. So that in every confiscation of security, the goods to be placed on it must be completely free from all encumbrances. But in fact the judge granted the request for confiscation of guarantees. So that when it is about to be executed, the execution cannot be executed. This is because the object of the confiscation of collateral has been previously pledged/guaranteed to PT. BPR Sumber Pangasean (Bank BSP), Tbk. Bandar Jaya Branch Office with Mortgage Rights. Efforts that can be taken by the plaintiff / applicant confiscation when the execution can not be executed, the execution can be transferred to another debtor items that are free from collateral impositiond